Is it all about European Democracy? The Motives behind the Institutionalisation of the Spitzenkandidaten Procedure - Lukáš Hamřík; Petr Kaniok (Journal of Contemporary European Research, 2019)
The European Parliament elections in 2014 and 2019 were different insofar as European citizens had the possibility to ‘directly’ influence who could become the next president of the European Commission. This innovation is based on the idea of ‘Spitzenkandidaten’, where a vote for a given political party also represents a vote for its lead candidate. This article examines the process behind the institutionalisation of the Spitzenkandidaten procedure, with attention focused on the actors involved and their motivations for supporting this institutional innovation. Using a qualitative content analysis of EU institutional and party documentation, the article confirms that the Spitzenkandidaten procedure should be perceived as the culmination of a long-term process beginning in the pre-Amsterdam era. It also concludes that the procedure, as firstly applied in 2014, represents the common effort of two supranational institutions and four European political parties. It is also argued that while the emergence of the Spitzenkandidaten is primarily a result of perceived shortcomings of the EU’s democratic quality, actors’ self-interest was also driving force.